Familial Hemiplegic Migraine and Spreading Depression - KAZEMI, Hadi; SPECKMANN, Erwin Josef; GORJI, Ali (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Kazemi H, Speckmann EJ, Gorji A. Familial Hemiplegic Migraine and Spreading Depression. Iran J Child Neurol. 2014 Summer;8(3): 6-11. Abstract Objective Familial hemiplegic migraine (FHM) is an autosomal dominantly inherited subtype of migraine with aura, characterized by transient neurological signs and symptoms. Typical hemiplegic migraine attacks start in the first or second decade of life. Some patients with FHM suffer from daily recurrent attacks since childhood. Results from extensive studies of cellular and animal models have indicated that gene mutations in FHM increase neuronal excitability and reduce the threshold for spreading depression (SD). SD is a transient wave of profound neuronal and glial depolarization that slowly propagates throughout the brain tissue and is characterized by a high amplitude negative DC shift. After induction of SD, S218L mutant mice exhibited neurological signs highly reminiscent of clinical attacks in FHM type 1 patients carrying this mutation. FHM1 with ataxia is attributable to specific mutations that differ from mutations that cause pure FHM1 and have peculiar consequences on cerebellar Cav2.1 currents that lead to profound Purkinje cell dysfunction and neuronal loss with atrophy. SD in juvenile rats produced neuronal injury and death. Hormonal factors involved in FHM affect SD initiation and propagation. The data identify SD as a possible target of treatment of FHM. In addition, FHM is a useful model to explore the mechanisms of more common types of migraine. References Russell MB, Ducros A. Sporadic and familial hemiplegic migraine: pathophysiological mechanisms, clinical characteristics, diagnosis, and management. Lancet Neurol 2011 (5):457-70. The International Classification of Headache Disorders, 3rd edition (beta version).Headache Classification Committee of the International Headache Society (IHS). Cephalalgia2013;33(9):629-808. Thomsen LL, Eriksen MK, Roemer SF, Andersen I, Olesen J, Russell MB.A population-based study of familial hemiplegic migraine suggests revised diagnostic criteria.Brain 2002a; 125(Pt 6):1379-91. Kazemi H, Gorji A. Migraine in children and adolescents. Iranian Journal of Child Neurology 2011; 4(4):1-6. Dichgans M, Mayer M, Uttner I, Brüning R, Müller-Höcker J, Rungger G, et al. The phenotypic spectrum of CADASIL: clinical findings in 102 cases. Ann Neurol 1998; 44(5):731-9. Prayson RA, Wang N. Mitochondrial myopathy, encephalopathy, lactic acidosis, and strokelike episodes (MELAS) syndrome: an autopsy report. Arch Pathol Lab Med 1998;122(11):978-81. Steele JG, Nath PU, Burn J, Porteous ME. An association between migrainous aura and hereditary haemorrhagic telangiectasia. Headache 1993;33(3):145-8. Haan J, Algra PR, Roos RA. Hereditary cerebral hemorrhage with amyloidosis–Dutch type.Clinical and computed tomographic analysis of 24 cases. Arch Neurol 1990;47(6):649-53. Gunel M, Awad IA, Anson J, Lifton RP.Mapping a gene causing cerebral cavernous malformation to 7q11.2-q21. ProcNatlAcadSci USA 1995;92:6620-4. Terwindt GM, Ophoff RA, Lindhout D, Haan J, Halley DJ, Sandkuijl LA, et al. Partial cosegregation of familial hemiplegic migraine and benign familial infantile epileptic syndrome. Epilepsia 1997;38(8):915-21. Bosemani T, Burton VJ, Felling RJ, Leigh R, Oakley C, Poretti A, Huisman TA.Pediatric hemiplegic migraine: Role of multiple MRI techniques in evaluation of reversible hypoperfusion.Cephalalgia2013 Oct 18.[Epub ahead of print]. Ducros A, Denier C, Joutel A, Cecillon M, Lescoat C, Vahedi K. The clinical spectrum of familial hemiplegic migraine associated with mutations in a neuronal calcium channel. N Engl J Med 2001;345:17-24. Thomsen LL, Eriksen MK, Roemer SF, et al. An epidemiological survey of hemiplegic migraine. Cephalalgia 2002b;22(5):361-75. Vahedi K, Depienne C, Le Fort D, Riant F, Chaine P, Trouillard O, et al.Elicited repetitive daily blindness: a new phenotype associated with hemiplegic migraine and SCN1A mutations. Neurology 2009 31;72(13):1178-83. Thomsen LL, Ostergaard E, Olesen J, Russell MB. Evidence for a separate type of migraine with aura: sporadic hemiplegic migraine. Neurology 2003;60(4):595-601. van den Maagdenberg AM, Haan J, Terwindt GM, Ferrari MD. Migraine: gene mutations and functional consequences. Curr Opin Neurol 2007; 20:299–305. Gritz SM, Radcliffe RA. Genetic effects of ATP1A2 in familial hemiplegic migraine type II and animal models. Hum Genomics 2013;5;7:8. Ophoff RA, Terwindt GM, Vergouwe MN, et al. Familial hemiplegic migraine and episodic ataxia type-2 are caused by mutations in the Ca2+ channel gene CACNL1A4. Cell 1996;87:543–552. Gargus JJ, Tournay A. Novel Mutation Confirms Seizure Locus SCN1A is Also Familial Hemiplegic Migraine Locus FHM3.PediatrNeurol 2007;37:407-410. Tottene A, Conti R, Fabbro A, Vecchia D, Shapovalova M, Santello M, et al.Enhanced excitatory transmission at cortical synapses as the basis for facilitated spreading depression in Ca(v)2.1 knockin migraine mice. Neuron 2009;61(5):762-73. Terwindt GM, Ophoff RA, Haan J, Sandkuijl LA, Frants RR, Ferrari MD. Migraine, ataxia and epilepsy: a challenging spectrum of genetically determined calcium channelopathies. Dutch Migraine Genetics Research Group. Eur J Hum Genet 1998;6(4):297-307. Terwindt GM, Ophoff RA, van Eijk R, Vergouwe MN, Haan J, Frants RR, et al. Dutch Migraine Genetics Research Group. Involvement of the CACNA1A gene containing region on 19p13 in migraine with and without aura. Neurology 2001;56(8):1028-32. Franceschini A, Vilotti S, Ferrari MD, van den Maagdenberg AM, Nistri A, Fabbretti E. TNFα levels and macrophages expression reflect an inflammatory potential of trigeminal ganglia in a mouse model of familial hemiplegic migraine. PLoS One 2013;8:e52394. Kodangattil JN, Möddel G, Müller, M, Weber W, Gorji A.The inflammatory chemokine CXCL10 modulates synaptic plasticity and neuronal activity in the hippocampus. European Journal of Inflammation 2012;10(3):311-328 Leao AAP. Spreading depression of activity in the cerebral cortex. JNeurophysiol 1944; 7: 359–390. Gorji A, Spreading depression: a review of the clinical relevance.Brain Res Brain Res Rev. 2001 Dec;38(1-2):33-60. Somjen GG.Mechanisms of spreading depression and hypoxic spreading depression-like depolarization. Physiol Rev 2001; 81(3):1065-96. Berger M, Speckmann EJ, Pape HC, Gorji A.Spreading depression enhances human neocortical excitability in vitro. Cephalalgia 2008;28(5):558-62. Ghadiri MK, Kozian M, Ghaffarian N, Stummer W, Kazemi H, Speckmann EJ, et al. Sequential changes in neuronal activity in single neocortical neurons after spreading depression.Cephalalgia 2012;32(2):116-24. Dreier JP, Major S, Pannek HW, Woitzik J, Scheel M, et al. COSBID study group.Spreading convulsions, spreading depolarization and epileptogenesis in human cerebral cortex.Brain 2012;135(Pt 1):259-75. Tokuda S, Kuramoto T, Tanaka K, Kaneko S, Takeuchi IK, Sasa M, et al.The ataxic groggy rat has a missense mutation in the P/Q-type voltage-gated Ca2+ channel alpha1A subunit gene and exhibits absence seizures. Brain Res 2007;1133(1):168-77. Ayata C, Shimizu-Sasamata M, Lo EH, Noebels JL, Moskowitz MA.Impaired neurotransmitter release and elevated threshold for cortical spreading depression in mice with mutations in the alpha1A subunit of P/Q type calcium channels. Neurosci 2000;95(3):639-45. van den Maagdenberg AM, Pizzorusso T, Kaja S, Terpolilli N, Shapovalova M, Hoebeek FE, et al. High cortical spreading depression susceptibility and migraine-associated symptoms in Ca (v)2.1 S218L mice. Ann Neurol 2010;67(1):85-98. Eikermann-Haerter K, Dileköz E, Kudo C, Savitz SI, Waeber C, Baum MJ, et al.Genetic and hormonal factors modulate spreading depression and transient hemiparesis in mouse models of familial hemiplegic migraine type 1.J Clin Invest 2009a;119(1):99-109. Eikermann-Haerter K, Yuzawa I, Qin T, Wang Y, Baek K, Kim YR, et al.Enhanced subcortical spreading depression in familial hemiplegic migraine type 1 mutant mice.J Neurosci 2011;31(15):5755-63. Eikermann-Haerter K, Dileköz E, Kudo C, Savitz SI, Waeber C, Baum MJ, et al.Genetic and hormonal factors modulate spreading depression and transient hemiparesis in mouse models of familial hemiplegic migraine type 1. J Clin Invest 2009b;119(1):99-109. Sachs M, Pape HC, Speckmann EJ, Gorji A.The effect of estrogen and progesterone on spreading depression in rat neocortical tissues.Neurobiol Dis 2007;25(1):27-34. Supcun B, Ghadiri MK, Zeraati M, Stummer W, Speckmann EJ, Gorji A.The effects of titanic stimulation on plasticity of remote synapses in the hippocampus-perirhinal cortex-amygdala network. Synapse2012;66(11):965-74. Eikermann-Haerter K, Baum MJ, Ferrari MD, van den Maagdenberg AM, Moskowitz MA, Ayata C.Androgenic suppression of spreading depression in familial hemiplegic migraine type 1 mutant mice.Ann Neurol 2009c;66(4):564-8. Freilinger T, Bohe M, Wegener B, Müller-Myhsok B, Dichgans M, Knoblauch H.Expansion of the phenotypic spectrum of the CACNA1A T666M mutation: a family with familial hemiplegic migraine type 1, cerebellar atrophy and mental retardation. Cephalalgia2008;28(4):403-7. Crawford JS, Konkol RJ.Familial hemiplegic migraine with crossed cerebellar diaschisis and unilateral meningeal enhancement.Headache 1997; 37(9):590-3. Candee MS, McCandless RT, Moore KR, Arrington CB, Minich LL, Bale JF Jr.White Matter Lesions in Children and Adolescents With Migraine. Pediatr Neurol 2013. [Epub ahead of print]. Jafarian M, Rahimi S, Behnam F, Hosseini M, Haghir H, Sadeghzadeh B, et al.The effect of repetitive spreading depression on neuronal damage in juvenile rat brain. Neurosci 2010;169(1):388-94. Sadeghian H, Jafarian M, Karimzadeh F, Kafami L, Kazemi H, Coulon P, Ghabaee M, Gorji A.Neuronal death by repetitive cortical spreading depression in juvenile rat brain.Exp Neurol 2012;233(1):438-46. Haghir H, Kovac S, Speckmann EJ, Zilles K, Gorji A.Patterns of neurotransmitter receptor distributions following cortical spreading depression.Neurosci 2009;163(4):1340-52. Kaube H, Herzog J, Käufer T, Dichgans M, Diener HC.Aura in some patients with familial hemiplegic migraine can be stopped by intranasal ketamine. Neurology 2000;55(1):139-41. Ayata C, Jin H, Kudo C, Dalkara T,Moskowitz MA.Suppression of cortical spreading depression in migraineprophylaxis. Ann Neurol 2006;59(4):652–661. Kazemi H, Rahgozar M, Speckmann EJ, Gorji A.Effect of cannabinoid receptor activation on spreading depression.Iran J Basic Med Sci 2012;15(4):926-36. Seghatoleslam M, Ghadiri MK, Ghaffarian N, Speckmann EJ, Gorji A. Cortical spreading depression modulates the caudate nucleus activity.Neuroscience 2014;267C:83-90. Eickhoff M, Kovac S, Shahabi P, Ghadiri MK, Dreier JP, Stummer W, Speckmann EJ, Pape HC, Gorji A. Spreading depression triggers ictaform activity in partially disinhibited neuronal tissues.Exp Neurol. 2014; 253:1-15.